Teknik ALBA untuk Meningkatkan Kemampuan Membaca dalam Pembelajaran Daring - Susanti, Susanti; Salim, Herli (Universitas Pendidikan Indonesia Kampus Serang, 2021)
This study aimed to determine the effect of using ALBA techniques online learning on students' reading skills. This research method used was quasi-experimental with treatment for the control and experimental classes. Data analysis descriptive and inferential statistics. In descriptive statistics to see the average test, the highest, and lowest scores. Inferential statistics are performed to test for normality, homogeneity, and average difference. The increase in the score was analyzed using a score gain. The results of the data analysis included (1) the increase in the score for the control class of 0.1 is included in the high classification, (2) the experimental class is 0.14 high, and (3) the increase in the post-test for the control and experimental class is 0.12 which is in the high classification. Based on the results of data analysis, it can be concluded that there are differences in the results of the ability test in the control class, experimental class in posttest in the control and experimental class. Learning to read the beginning using the ALBA technique in online learning has a good effect according to the results of interviews. This technique makes it easier for students to accelerate reading primary school students.